A Framework for Compiling Quantifications of Marine Biosecurity Risk Factors Associated With Common Vessel Types - Tzeng, Mimi W.; Floerl, Oliver; Zaiko, Anastasija (Frontiers in Marine Science, 2021)
Globally, movements of commercial vessels can facilitate the spread of marine non-indigenous species (NIS) beyond their current biogeographic ranges. Authorities at potential destination locations employ a number of biosecurity risk assessment strategies to estimate threat levels from potential origin locations, vulnerability levels of specific destination regions, or the consequences of successful establishment of particular NIS species. Among the many factors and processes that have an influence on the probability that NIS will survive transport and establish successfully at new locations, vessel type has been identified as an important risk factor. Different vessel types have different structural and operational characteristics that affect their overall level of marine biosecurity risk. Several recent studies have examined subsets of vessel types or vessel characteristics for their ability to spread NIS. While high-quality information is available via these endeavors, it is fragmented and not readily available as an integrated resource to support biosecurity regulators or other end-users. In this study, we synthesize available empirical data on a wide range of vessel types and characteristics to develop a framework that allows systematic quantification of the relative risk of NIS transfer by common commercial vessel types. We explain our approach for constructing the framework, from selection of key risk factors for inclusion, to selection of which datasets to use for those risk factors. The framework output is a set of risk scores which denote the relative biosecurity risk of common commercial vessel types. To demonstrate a potential application of our framework, we applied the risk scores to vessel visit data for commercial ports around New Zealand and assigned a relative risk level per port based on the arrival frequencies of different vessel types. The resulting per-port risk levels matched closely with the results of a prior benchmark study that employed state-of-the-art risk modeling approaches. Our framework is based on globally relevant data, is simple to implement, and is adaptable as new empirical information arises. It can serve as a simple tool to determine the relative levels of vessel-related biosecurity risk associated with geographic shipping hubs, or it can be used as a vessel-specific “risk mask” for maritime transport models. It can be applied to any scientific or policy question that requires information on vessel type differences in relation to marine biosecurity risk.